Can circulating oxidative stress-related biomarkers be used as an early prognostic marker for COVID-19? - Uysal, Pelin; Yüksel, Arzu; Durmus, Sinem; Cuhadaroglu, Çaglar; Gelisgen, Remise; Uzun, Hafize (Frontiers in Medicine, 2023)
Background Oxidative stress plays an important role in the pathogenesis of many diseases. This study aimed to investigate the relationship between nuclear factor kappa B (NF-κB) and oxidative stress and the severity of the disease in new COVID-19 patients, and, to compare the levels of NF-κB, oxidized LDL (oxLDL), and lectin-like oxidized-LDL receptor-1 (LOX-1) with oxygen saturation, which is an indicator of the severity parameters of the disease in COVID-19 patients. Methods In this prospective study, 100 COVID-19 patients and 100 healthy subjects were selected. Results LOX-1, NF-κB, and oxLDL were found to be higher in COVID-19 patients compared to the healthy subjects (p < 0.001 for all). According to the results of correlation analysis, it was found that there was no significant relationship between oxygen saturation and LOX-1, NF-κB and oxLDL parameters. There was significant relationship between oxLDL with LOX-1 and NF-κB in patients with COVID-19 disease. ROC analysis results of the highest discrimination power were oxLDL (AUC: 0.955, CI: 0.904–1.000; sensitivity: 77%, and specificity: 100%, for cutoff: 127.944 ng/l) indicating COVID-19. Conclusion Oxidative stress plays an essential role in COVID-19. NF-κB, oxLDL, and LOX-1 seem to represent good markers in COVID-19. Our study also showed that oxLDL has the highest power in distinguishing patients with COVID-19 from the healthy subjects.